Phytochemical constituents and antioxidant activities of banana flower of Musa x paradisiaca - Mahmood, Azizah; Omar, Muhammad Nor; Ngah, Nurziana (2010)
Frequent consumption of fruits and vegetables is associated with a lowered risk of cancer, heart disease, hypertension and stroke. This has been attributed to the presence of various forms of phytochemical and antioxidants in the foods. Pisang Nipah (Musa x paradisiaca) was analysed in this study for its tannin, flavanoid, alkaloid, total phenolic content and antioxidant activities. Quantitative estimation of tannin, flavanoid and total phenolic were analyzed by uv-visible spectrophotometer, while saponin and alkaloid were analyzed by gravimetric method. Current study shows that banana flower contains crude chemical constituents of tannin(7.83%) flavanoid(0.16%) saponin(1.43%) alkaloid(1.56%) and total phenolic(2.98%). The antioxidant activity of the flower extracts was determined using the 1-diphenyl-2-picrylhydrazyl(DPPH) free radical scavenging assay. The study shows potent antioxidant activity in banana flowers, of which the ethanol extract demonstrated much stronger antioxidant activity than water extract with the IC50 value of 29.75mg/ml and 1.52mg/ml, respectively. Increasing the concentration of the extract resulted in reducing the colour of DPPH solution. This study shows that antioxidative activities of banana flower may be a potential source of natural antioxidants with similar characteristics to the synthetic antioxidant, butylated hyroxyanisole (BHT).